Fibroblast Growth Factor-21 to Adiponectin Ratio: A Potential Biomarker to Monitor Liver Fat in Children With Obesity - Tas, Emir; Bai, Shasha; Ou, Xiawei; Mercer, Kelly; Lin, Haixia; Mansfield, Kori; Buchmann, Robert; Diaz, Eva C.; Oden, Jon; Børsheim, Elisabet; Adams, Sean H.; Dranoff, Jonathan (Frontiers in Endocrinology, 2020)
Background. There is a pressing need for effective and non-invasive biomarkers to track intrahepatic triglyceride (IHTG) in children at-risk for non-alcoholic fatty liver disease (NAFLD), as standard-of-care reference tools, liver biopsy and magnetic resonance imaging (MRI), are impractical to monitor the course disease. Objective. We aimed to examine the association between serum fibroblast growth factor (FGF)-21 to adiponectin ratio (FAR) and IHTG as assessed by MRI in children with obesity. Methods. Serum FGF21 and adiponectin levels and IHTG were measured at two-time points (baseline, 6 months) in obese children enrolled in a clinical weight loss program. The association between percent change in FAR and IHTG at the final visit was examined using a multiple linear regression model. Results. At baseline, FAR was higher in the subjects with NAFLD (n=23, 35.8 ± 41.9 pg/ng) than without NAFLD (n=35, 19.8 ± 13.7 pg/ng; p=0.042). Forty-eight subjects completed both visits and were divided into IHTG loss (≥1% reduction than baseline), no change (within 1% change), and gain (≥1% increase than baseline) groups. At 6 months, the percent change in FAR was different among the three groups (p=0.005). Multiple linear regression showed a positive relationship between percent change in FAR and the final liver fat percent in sex and pubertal stage-similar subjects with NAFLD at baseline (slope coefficient 6.18, 95% CI 1.90 to 10.47, P=0.007), but not in those without NAFLD. Conclusions. Higher value in percent increase in FAR is positively associated with a higher level of IHTG percent value at 6 months in children with baseline NAFLD. FAR could be a potential biomarker to monitor the changes in IHTG in children with NAFLD.